A Constructive Model of MSMEs’ Entrepreneurial Success Based on Green Management System and Psychological Capital in Semarang City - Wiratno Putri, V; Ridloah, S; Rafinda, A (KnE Social Sciences, 2018)
The study has purpose to identify the factors of entrepreneurial success by involving psychological factor and managerial skills factor with knowledge of the environment in SMEs in Semarang City in order to increase the success of entrepreneurship companies through competitive advantage. The population in this study is the owners of small and medium scale businesses or managers (general manager) in Semarang City. The required sample is 180 respondents who have experience in managing the business. Quantitative and qualitative analysis were used as the method of this study. The researchers conducted observations by distributing the questionnaires and interviews on SMEs regarding to psychological factors, social factors, understanding of business insight, managerial and competitive advantage. Structural equation modeling (SEM) with WarpPLS program application was used as the analytical tool. The results show that the contribution of psychological factors and environmental managerial capabilities of SMEs to competitive advantage and SME entrepreneurship success in the city of Semarang. Thus, the success of entrepreneurship in the future is not only oriented to the operational quality capability of the SME actors, but the psychological and behavioral things that are environmentally sound from the SME actors, which also need to be developed. Keywords: SME, Competitive Advantage Strategy, Green Management, Psychological capital, entrepreneurial success.